The role of experience in children’s discrimination of unfamiliar languages - Potter, Christine E.; Saffran, Jenny R. (Frontiers in Psychology, 2015)
Five- and six-year-old children (n=160) participated in three studies designed to explore language discrimination. After an initial exposure period (during which children heard either an unfamiliar language, a familiar language, or music), children performed an ABX discrimination task involving two unfamiliar languages that were either similar (Spanish vs. Italian) or different (Spanish vs. Mandarin). On each trial, participants heard two sentences spoken by two individuals, each spoken in an unfamiliar language. The pair was followed by a third sentence spoken in one of the two languages. Participants were asked to judge whether the third sentence was spoken by the first speaker or the second speaker. Across studies, both the difficulty of the discrimination contrast and the relation between exposure and test materials affected children’s performance. In particular, language discrimination performance was facilitated by an initial exposure to a different unfamiliar language, suggesting that experience can help tune children’s attention to the relevant features of novel languages.